A Comparison of the Efficacy and Safety of Denosumab and Zoledronic Acid in Patients with Bone Metastatic Breast Cancer Receiving CDK4/6 Inhibitor Therapy - İrem Öner; Hicran Anık; Bediz Kurt İnci; Pınar Kubilay Tolunay; Öztürk Ateş; Ülkü Yalçıntaş Arslan; Cengiz Karaçin (Medicina)
Background and Objectives: Bone metastases in patients can cause significant quality-of-life declines due to skeletal-related events (SREs). SRE is defined as the occurrence of radiotherapy for bone pain, pathologic fracture, bone surgery, spinal cord compression, or hypercalcemia. Bone-modifying agents (BMAs), such as denosumab and zoledronic acid, are crucial in reducing the frequency and severity of SREs. The inhibition of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors has emerged as the standard treatment for hormone receptor-positive metastatic breast cancer, demonstrating significant improvements in survival outcomes. This study aims to compare the effectiveness of denosumab and zoledronic acid in preventing SRE in patients receiving CDK4/6 inhibitors with endocrine therapy. Materials and Methods: This retrospective study included 328 patients diagnosed with bone metastatic breast cancer receiving first-line CDK4/6 inhibitor therapy (palbociclib or ribociclib). Patients were assigned to receive either subcutaneous denosumab or intravenous zoledronic acid every 4 weeks. Time to the first skeletal-related event post bone-modifying agent initiation, SRE incidence, and the safety data were evaluated. The data were analyzed using independent samples t-tests, chi-square tests, and Kaplan–Meier methods for time-to-event data. Results: In the denosumab group, the median time to the first skeletal-related event was significantly longer than in the zoledronic acid group (44.55 months and 29.16 months, respectively). Denosumab treatment was associated with a statistically significant reduction in the risk of developing the first SRE after bone-modifying agent initiation compared to zoledronic acid (HR: 0.56, p = 0.001). Additionally, ECOG PS and the number of metastatic bone sites were identified as independent prognostic factors for time to the first SRE. The safety profile was consistent with previous studies reported in the literature. Conclusions: Our study demonstrated that when used with CDK4/6 inhibitors, denosumab is associated with a delay in SREs and a lower SRE incidence than zoledronic acid in patients with bone metastases. These findings support the efficacy of denosumab in preventing SREs and suggest that CDK4/6 inhibitors may have distinct effects on the bone microenvironment, particularly when combined with denosumab.